Description and function of a difficult airway service. Issue 3 (26th December 2019) - Murray, David J.; Massy‐Westropp, Collette; Narayana‐Reddy, Kavya; Marsh, Jennifer
Abstract: The goal of the Pediatric Difficult Airway Service (DAS) is to improve the care of children with airway abnormalities primarily through identification of children at risk for failed airway management. The airway service encourages early recognition and provides consultation, a plan for airway management, expertise in airway management, and follow‐up care for children who have a difficult airway. The service has improved the education of healthcare professionals and heightened awareness about the consequences of failed airway management.